2021
DOI: 10.1002/ecs2.3550
|View full text |Cite
|
Sign up to set email alerts
|

Management‐mediated predation rate in the caribou–moose–wolf system: spatial configuration of logging activities matters

Abstract: Landscape complexity can determine the population dynamics of interacting predators and prey. Yet, management plans are commonly developed from aspatial predictive models. This oversight may result in unexpected outcomes or the loss of opportunities to make spatial interventions that would increase a plan's effectiveness. The management of the threatened woodland caribou (Rangifer tarandus caribou), boreal population, provides an example of such shortcomings when using an aspatial approach. Currently, the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 77 publications
3
15
0
Order By: Relevance
“…Empirical studies showed that wolves hunt by targeting areas rich in moose's food, including disturbed areas where early-seral vegetation has emerged 42,43 . While the behavioral response had significant but minor effects on mortality per se, our findings are consistent with previous studies reporting that the increased disturbance rates 43,44 , resource availability 28,41,45 , and changes in landscape structure 13,40 altered predator-prey interactions in many systems. For example, changes in land use can modify how water vole (Arvicola terrestris) habitat patch was connected to surrounding rabbit (Oryctolagus cuniculus) habitat, triggering apparent competition between the two prey species through a shared predator, the American mink (Neovison vison), with subsequent negative effects on the probability of water vole habitat patch occupancy 13 .…”
Section: Main Textsupporting
confidence: 91%
See 2 more Smart Citations
“…Empirical studies showed that wolves hunt by targeting areas rich in moose's food, including disturbed areas where early-seral vegetation has emerged 42,43 . While the behavioral response had significant but minor effects on mortality per se, our findings are consistent with previous studies reporting that the increased disturbance rates 43,44 , resource availability 28,41,45 , and changes in landscape structure 13,40 altered predator-prey interactions in many systems. For example, changes in land use can modify how water vole (Arvicola terrestris) habitat patch was connected to surrounding rabbit (Oryctolagus cuniculus) habitat, triggering apparent competition between the two prey species through a shared predator, the American mink (Neovison vison), with subsequent negative effects on the probability of water vole habitat patch occupancy 13 .…”
Section: Main Textsupporting
confidence: 91%
“…Our research adds to a growing body of evidence that specialist species of low productive environment may be vulnerable to landscape structure that affect the distribution of predation risk 40,41 . Empirical studies showed that wolves hunt by targeting areas rich in moose's food, including disturbed areas where early-seral vegetation has emerged 42,43 .…”
Section: Main Textmentioning
confidence: 89%
See 1 more Smart Citation
“…Co‐occurrence of black bears with white‐tailed deer also decreased with increasing harvest block area, indicating that block size may influence predator–prey dynamics. Previous research suggests that forest edges are important for bears, primary prey species and predator–prey interactions (Fortin et al, 2015; Murphy et al, 2021; Vanlandeghem et al, 2021), and the open spaces distant from forest cover created by larger harvest blocks may deter use of these blocks by deer and bears. In addition, seismic line density in the surrounding area influenced the co‐occurrence of grizzly bears with mule deer, while harvest block density in the surrounding area influenced co‐occurrence of black bears and grizzly bears with elk, providing further evidence that the surrounding anthropogenic disturbance also influences co‐occurrence and wildlife use of harvest blocks at the site level.…”
Section: Discussionmentioning
confidence: 99%
“…Direct predator removal is an ecologically improbable task that could result in undesirable outcomes including trophic cascades, net population increases of the removed predator, or increases in sympatric or co‐occurring carnivores (Prugh et al 2009, Estes et al 2011). It may be possible, however, to indirectly mitigate predation risk for martens, other subordinate carnivores, or prey species by decreasing the foraging efficacy of predators (Vanlandeghem et al 2021). At broad (Cushman et al 2011, Zielinski 2014, Aylward et al 2020) and fine scales (Tweedy et al 2019), martens are generally associated with structurally heterogeneous forest cover and often avoid areas with reduced cover (Moriarty et al 2016), rarely enter openings during snow‐free periods (Moriarty et al 2015, Martin et al 2021), and exhibit increased movement rates and energetic expenditures in simplified forest stands (Moriarty et al 2016, Martin et al 2020).…”
Section: Discussionmentioning
confidence: 99%